PILOT PROJECT DIGITAL MARKETING FOR SMALL SCALE BUSINESS IN BLITAR - Sanhari Prawiradiredja; Budi Santoso; Citra Rani Angga Riswari (Institut Bisnis dan Teknologi Pelita Indonesia, 2023)
This community service will be carried out in Dayu village, Nglegok sub-district, Blitar district. This area has become an object of service because of the existence of an organization called Pertakina that fosters small-scale economic enterprises. This community service is carried out in Dayu Village, Nglegok District, Blitar Regency. This area has become an object of service because there is Pertakina, which is an organization that has a number of small scale business managed by former PMI (Indonesian Migrant Workers). They belong to a group of Indonesian migrant workers who with their own capital are trying to be economically independent, so they no longer need to work abroad to earn income. Pertakina has members with various categories (a) former migrant workers, (b) families of migrant workers who own or are starting a business, (c) residents who join to become independent entrepreneurs. Until now, PERTAKINA has recorded 68 members of whom already have businesses and 82 people are starting businesses. The problem they face is how to increase marketing to increase production scale. Therefore, what must be done is to foster a pioneering spirit of doing business for former overseas migrant workers so that they can become independent entrepreneurs and can work in peace with their families. Some of the problems faced by small scale business actors are (1) Some business actors do not yet have a brand or brand for their business or products, (2) Already have an institutional web but do not have media for displaying digital products (3) Business is handled domestically so it requires connectivity and wider range of business.With the emergence of these problems, the community service team developed programs, namely: (1) brand development training by increasing product value with presentation of photographic displays, (2) Creating web-commerce featuring variations of products. With the existence of this website, it will become a display case for Pertakina products, (3) The use of social media for small scale business independently in marketing their products is through Instagram and Youtube media.